Developing an expandable ferric tannate/gallate polyurethane sponge evaporator for efficient solar desalination. (25th February 2023) - Guo, Chenglong; Zhang, Wenting; Liu, Ke; Zhang, Tongxing; Liu, Qi; Cao, Hongxia; Li, Lin
Highlights: Ferric tannate/gallate with full-spectrum absorption was prepared. Expandable ferric tannate/gallate polyurethane sponge evaporator was developed. Evaporation rate of 1.76 kg m −2 h −1 was achieved at 1 kW m −2 illumination. The prepared evaporator possessed excellent recyclability and salt tolerance. Abstract: Solar desalination has been extensively investigated as a promising candidate for solving freshwater shortage but developing an expandable evaporator with excellent salt resistance and evaporation performance is still a challenge in practical application. In this work, inspired by the color effect between abandoned tea and rusty iron nails, a ferric tannate/gallate with full-spectrum absorption and low cost characteristics was prepared as a high-performance photothermal conversion material and further employed to develop an expandable ferric tannate/gallate polyurethane sponge evaporator for efficient solar desalination accompanied by outstanding salt resistance in NaCl solution with high salinity. The results showed that the developed evaporator had an evaporation rate of 1.76 kg m −2 h −1 with a corresponding evaporation efficiency of 89.7 % at 1 kW m −2 illumination. Moreover, this evaporator possessed splendid recyclability and superior salt tolerance in 20 wt% NaCl solution due to its hydrophilicity and sufficient transport channels for salt and water. It was also proved by outdoor experiment that the system with 1 m 2 evaporator was able to provide more than 7.5 kg freshwater per day for satisfying individual daily survival demand. This work demonstrated that an easy-to-implement and practical expandable ferric tannate/gallate polyurethane sponge evaporator exhibited enormous potential in the field of solar desalination.